Accelerated institutionalization of an adolescent sexual and reproductive health (ASRH) intervention in Tanzania: Findings from a mixed-methods evaluation - Cutherell, Meghan; Bwire, Juliana; Mtei, Edwin; Musau, Abednego; Kahabuka, Catherine; Luhanga, Isabellah; Julius, Augustino; Kihwele, Gerald (Frontiers in Global Women's Health, 2023)
Introduction: From 2018 to 2020 Adolescents 360 (A360), aiming to increase demand for and voluntary uptake of modern contraception among adolescent girls 15-19 years, designed and scaled an intervention in Tanzania, Kuwa Mjanja, to 13 regions through project-funded expansion. In 2020 the project developed a strategy for its follow-on phase, focusing on sustainability. In this process, funder priorities led to a decision to exit A360’s programming in Tanzania over a 15-month period. A360 elected to pursue a process of expedited institutionalization of Kuwa Mjanja into government systems during this period. Materials and Methods: The institutionalization process was facilitated in 17 local government authorities in Tanzania. Quantitative and qualitative data was gathered and analyzed including time-trend analysis of routine performance data, statistical analysis of two rounds of client exit interviews, and thematic analysis of qualitative research. Results: The socio-demographic characteristics of adolescent girls reached under government-led implementation were comparable to those reached by A360-led implementation. Intervention productivity decreased under government-led implementation but remained consistent. Adopter method mix shifted slightly towards greater LARC uptake under a government-led model. Factors which enabled successful institutionalization of Kuwa Mjanja included the presence of youth-supportive policies, the establishment of school clubs which provided SRH education, commitment of government stakeholders, and appreciation of adolescent pregnancy as a problem. Some intervention components were important for program effectiveness but proved difficult to institutionalize, primarily because of resource constraints. Lack of ASRH-focused targets and indicators disincentivized Kuwa Mjanja implementation. Discussion: There is significant potential in operationalizing user-centered ASRH models within government structures, even in a narrow time frame. A360 saw similar performance under government-led implementation and fidelity to the unique experience that the program was designed to deliver for adolescent girls. However, beginning this process earlier presents greater opportunities, as some aspects of the institutionalization process which are critical to sustained impact – for example shifting government policy and measurement and mobilizing government resources – require heavy coordination and long-term efforts. Programs pursuing institutionalization in a shorter time frame would benefit from setting realistic expectations. This may include prioritizing a smaller sub-set of program components that have the greatest impact.